Spatio and temporal spread of Plum pox virus infecting European plum (Prunus domestica L. cv. D'agen) orchard in Mendoza, Argentina = Distribución espacial y temporal del Plum pox virus en un monte de ciruelo europeo (Prunus domestica L cv D'agen) de Mendoza, Argentina - Dal Zotto, Angelica (2020)
Sharka, caused by Plum pox virus (PPV), is considered one of the most serious viral diseases of stone fruits worldwide due to the great yield losses in orchards. In Rama Caída, Mendoza, a 5-year study (2007-2011) was conducted on the degree of disease dispersion in a European plum cv D’agen orchard using samples from leaves and DAS-ELISA assay against PPV in order to determine incidence over time and spatial spread. Incidence significantly increased between 2007 and 2009 and during the next two years the increase was not statistically significant. Spatial point pattern of PPV at the plot was characterized by the occurrence of some heterogeneous clusters of infected trees located up to 65 m in the west-east direction of the rows over the five years. Point pattern and correlation type-approaches were undertaken using joint-count and Ripley's K function and showed that the detected infected plants had a disease aggregation pattern both in west-east and south-north directions, and within row and between rows across the plot. This short-distance local dispersion would be associated with diverse factors, such as vector aphids, that were not evaluated in this study. Hence, this work can serve as a basis for further studies in sharka dispersion in Cuyo region.